1988
DOI: 10.1002/ijc.2910410121
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of simian immunodeficiency virus from african green monkeys and seroepidemiologic survey of the virus in various non‐human primates

Abstract: Sixteen isolates of simian retrovirus closely related to human immunodeficiency virus (HIV) were obtained from healthy African green monkeys (AGM) (Cercopithecus aethiops). The first isolate was obtained from a monkey seropositive for HIV, and the others were isolated from monkeys harboring antibodies to the first isolate. These simian retroviruses were referred to as simian immunodeficiency virus from AGM, SIV[AGM], due to their cross-reactivities with HIV structural proteins. These SIV[AGM] isolates were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
169
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(175 citation statements)
references
References 36 publications
5
169
1
Order By: Relevance
“…Since the discovery of HIV-1 and HIV-2, surveys of nonhuman primate species have indicated that related viruses are widespread in a large number of African primate species (18,21). Thirty species with serological evidence of SIV infection have already been identified, and in 27 this was confirmed by partial or full-length genome sequencing, highlighting the increasing complexity of phylogenetic relationships among primate lentiviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of HIV-1 and HIV-2, surveys of nonhuman primate species have indicated that related viruses are widespread in a large number of African primate species (18,21). Thirty species with serological evidence of SIV infection have already been identified, and in 27 this was confirmed by partial or full-length genome sequencing, highlighting the increasing complexity of phylogenetic relationships among primate lentiviruses.…”
Section: Discussionmentioning
confidence: 99%
“…19 Negative controls were sterile water and DNA from an HTLV-negative T cell mers for a single copy gene, the endogenous retrovirus sequence ERV-3, 16 and only samples positive in this assay line, MOLT-4. 20 The sensitivity of PCR was determined by serial dilution of DNA from the cell line C10/PBL, which contains were further processed.…”
mentioning
confidence: 99%
“…These primate retroviruses, called simian immunodeficiency viruses (SIVs), were isolated from rhesus macaques Macaca mulatta (SIVMAc) , sooty mangabeys Cercocebus atys (SIVsM) (Fultz et al, 1986;Lowenstine et al, 1986;Murphey-Corb et al, 1986), African green monkeys Cercopithecus aethiops (SIVAGM) (Ohta et al, 1988), a cynomolgus macaque Macacafascicularis (Daniel et al, 1988a), a stump-tailed macaque Macaca arctoides (SIVstM) (Lowenstine et al, 1988), and a pigtailed macaque Macaca nemestrina (SIVMn¢) . These primate retroviruses are lentiviruses and share morphological and antigenic characteristics with HIV (Schneider & Hunsmann, 1988).…”
mentioning
confidence: 99%
“…SIVMAc, SIVsM, SIVstM and SIVMn¢ induce an AIDS-like disease in rhesus monkeys Murphey-Corb et al, 1986;Lowenstine et al, 1988;Benveniste et al, 1988). However, the pathogenicity of SIVsM and SIVAcM in their natural African primate hosts has not been documented (Fultz et al, 1986;Ohta et al, 1988). As SIV infection of rhesus macaques provides a useful animal model for HIV pathogenesis, the characterization of the 0000-9016 © 1990 SGM antigenic relationships among HIV and SIV isolates will help in the understanding of the history and evolution of these primate lentiviruses.…”
mentioning
confidence: 99%
See 1 more Smart Citation